Feasibility of robot-based perturbed-balance training during treadmill walking in a high-functioning chronic stroke subject: a case-control study - Matjačić, Zlatko; Zadravec, Matjaž; Olenšek, Andrej (Journal of neuroengineering and rehabilitation, 2018)
Background For stroke survivors, balance deficits that persist after the completion of the rehabilitation process lead to a significant risk of falls. We have recently developed a balance-assessment robot (BAR-TM) that enables assessment of balancing abilities during walking. The purpose of this study was to test feasibility of using the BAR-TM in an experimental perturbed-balance training program with a selected high-functioning stroke survivor. Methods A control and an individual with right-side chronic hemiparesis post-stroke were studied. The individual post-stroke underwent thirty sessions of balance-perturbed training that involved walking on an instrumented treadmill while the BAR-TM delivered random pushes to the participant’s pelvis; these pushes were in various directions, at various speeds, and had various perturbation amplitudes. We assessed kinematics, kinetics, electromyography, and spatio-temporal responses to outward-directed perturbations of amplitude 60 N (before training) and 60 N and 90 N (after training) commencing on contact of either the nonparetic-left foot (LL-NP/L perturbation) or the paretic-right foot (RR-P/R perturbation) while the treadmill was running at a speed of 0.4 m/s. Results Before training, the individual post-stroke primarily responded to LL-NP/L perturbations with an in-stance response on the non-paretic leg in a similar way to the control participant. After training, the individual post-stroke added adequate stepping by making a cross-step with the paretic leg that enabled successful rejection of the perturbation at lower and higher amplitudes. Before training, the individual post-stroke primarily responded to RR-P/R perturbations with fast cross-stepping using the left, non-paretic leg while in-stance response was entirely missing. After training, the stepping with the non-paretic leg was supplemented by partially recovered ability to exercise in-stance responses on the paretic leg and this enabled successful rejection of the perturbation at lower and higher amplitudes. The assessed kinematics, kinetics, electromyography, and spatio-temporal responses provided insight into the relative share of each balancing strategy that the selected individual post-stroke used to counteract LL-NP/L and RR-P/R perturbations before and after the training. Conclusions The main finding of this case-control study is that robot-based perturbed-balance training may be a feasible approach. It resulted in an improvement the selected post-stroke participant’s ability to counteract outward-directed perturbations. Trial registration ClinicalTrials.gov Identifier: NCT03285919 – retrospectively registered.